2013
DOI: 10.5688/ajpe775104
|View full text |Cite
|
Sign up to set email alerts
|

Active-Learning Instruction on Emergency Contraception Counseling

Abstract: Objective. To increase pharmacy students' knowledge of and confidence in counseling patients regarding emergency contraception and to identify any barriers to counseling patients about emergency contraception.Design. Approximately 200 third-year pharmacy students participated in the Women's Health Therapeutics workshop at Midwestern University Chicago College of Pharmacy. Students observed a 5-minute skit of a counseling session on emergency contraception and then were asked to pair up with a classmate and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…This may also provide an opportunity for counseling about other forms of contraception and sexually transmitted infection prevention. Recent studies have shown the important role pharmacists play in patient counseling and the ability of pharmacy students to confidentially counsel patients after an active-learning exercise [15,16]. However, patients may encounter a pharmacist who has a personal moral objection to EC, as one of our simulated patients did in a single encounter, which creates an additional access barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This may also provide an opportunity for counseling about other forms of contraception and sexually transmitted infection prevention. Recent studies have shown the important role pharmacists play in patient counseling and the ability of pharmacy students to confidentially counsel patients after an active-learning exercise [15,16]. However, patients may encounter a pharmacist who has a personal moral objection to EC, as one of our simulated patients did in a single encounter, which creates an additional access barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have raised concerns about pharmacy students' knowledge of emergency contraception. 10 , 16 Young et al 11 found that pharmacy students at the University of Arkansas had several knowledge deficits related to oral levonorgestrel. Like our findings, only one-third of students knew the mechanism of action of oral levonorgestrel.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents self-reported demographic characteristics, including age, race, ethnicity, gender identity, year in pharmacy school, religious affiliation, number of hours of formal education on emergency contraception, and what sources they used to learn about emergency contraception. These demographic characteristics were collected because age, 8 gender, 9 11 ethnicity, 9 religion, 9 , 11 13 year of training, 10 , 14 hours of education, 14 and source of knowledge acquisition 14 have been associated with differences in student, resident, and pharmacist knowledge and/or pharmacist practice patterns. Pharmacy student knowledge of the availability, side effects, mechanisms of action, and purchasing access was assessed through 24 questions (20 true/false and 4 multiple choice).…”
Section: Methodsmentioning
confidence: 99%
“…In 2013 Young et al(n=189) found that approximately 25% of students stated they were confident in counseling patients regarding EC prior to an active-learning exercise compared to 59% after (p < .01). 20 Students were asked to rate the degree to which certain barriers hindered their ability to counsel on EC utilizing a scale of 0 to 100, with 0 representing "not a barrier" and 100 representing "it's a definite barrier." The most common barrier to counseling identified by students on the pre-and post-workshop survey was lack of knowledge (presurvey mean score 41.0 and postsurvey mean score 19.8, p < 001).…”
Section: Emergency Contraceptionmentioning
confidence: 99%